2013
DOI: 10.1016/j.bbamem.2012.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Thellungiella salsuginea dehydrins TsDHN-1 and TsDHN-2 with membranes at cold and ambient temperatures—Surface morphology and single-molecule force measurements show phase separation, and reveal tertiary and quaternary associations

Abstract: Dehydrins (group 2 late embryogenesis abundant proteins) are intrinsically-disordered proteins that are expressed in plants experiencing extreme environmental conditions such as drought or low temperature. Their roles include stabilizing cellular proteins and membranes, and sequestering metal ions. Here, we investigate the membrane interactions of the acidic dehydrin TsDHN-1 and the basic dehydrin TsDHN-2 derived from the crucifer Thellungiella salsuginea that thrives in the Canadian sub-Arctic. We show using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 98 publications
0
22
1
Order By: Relevance
“…A transmembrane pore-lining stretch in AhDHN was assigned for the residues I127-Y142 (Figures 5 and 6). In fact, DHNs were recorded to be localized to plasma membranes during cold acclimation in wheat (Danyluk et al, 1998) and in Thellungiella salsuginea (Rahman et al, 2013). Borovskii et al (2002) found that DHNs can accumulate in mitochondria in response to cold, freezing, and drought in cereals.…”
Section: Discussionmentioning
confidence: 99%
“…A transmembrane pore-lining stretch in AhDHN was assigned for the residues I127-Y142 (Figures 5 and 6). In fact, DHNs were recorded to be localized to plasma membranes during cold acclimation in wheat (Danyluk et al, 1998) and in Thellungiella salsuginea (Rahman et al, 2013). Borovskii et al (2002) found that DHNs can accumulate in mitochondria in response to cold, freezing, and drought in cereals.…”
Section: Discussionmentioning
confidence: 99%
“…However, examination of the CD spectra of both proteins shows that there is no gain of α-helicity, suggesting a different mode of binding compared to ZmDHN1 (Koag et al, 2003). Using Fourier-transformed infrared spectroscopy (FTIR), Rahman et al (2013) showed that for Thellungiella salsuginea dehydrin 1 (TsDHN-1) the type and amount of structural change was dependent on lipid type, where they detected the gain of some β-strand structure for this protein when bound to lipid compositions mimicking the plasma membrane, mitochondrial membrane and chloroplast membrane (Rahman et al, 2010, 2013). It is challenging to reconcile the gain of β-strand structure compared to the α-helical structure seen in other studies for dehydrins bound to membranes, since the plasma membrane mimicking vesicles contain phospholipids.…”
Section: Dehydrin Ligandsmentioning
confidence: 99%
“…Five proteins (LEA4, 5, 8, 10, and 33) belonging to the dehydrin family could interact with the plasma membrane since LEA5, LEA10, and LEA33 have been shown to bind anionic phospholipid vesicles (Kovacs et al, 2008;Eriksson et al, 2011). Moreover, dehydrins from maize (Zea mays) and the salt-tolerant Thellungiella salsuginea have also been shown to bind phospholipid vesicles (Koag et al, 2003(Koag et al, , 2009Rahman et al, 2010Rahman et al, , 2013. Interestingly, four dehydrins (LEA4, 5, 8, and 10) with a clear cytosolic localization in our experiments were also identified in chloroplast proteome (Kleffmann et al, 2004;Zybailov et al, 2008;Ferro et al, 2010;Kong et al, 2011) or in the tonoplast in the case of LEA10 (Whiteman et al, 2008).…”
Section: Cytosolic and Nuclear Lea Proteinsmentioning
confidence: 99%